CONTRIBUTION TO TURKISH LANGUAGE MAP: IN LEBANON TURKS AND TURKISH - Özgür Kasım AYDEMİR (Zeitschrift für die Welt der Türken, 2013)
Article, field study within the borders of Lebanon, aims to share general information on issues to be spoken Turkish. Today, as much as 30000 citizens living in Lebanon for nearly 12000 to be registered. Most of these countries are settled in 1940 after the Turks to come to work. However, the Turks settled in Lebanon after 1940, as well as the more they leave any kind of Arabic language features that reflect the geography of this work is not subject to due. In this study, the number 13200 Turkmen living in this region in the 13th century, which approximate number 9000, 19th living within the borders of Lebanon since the end of the century the Turks and their language is focused on the muhajir of Crete. Turkish Arabic code to be very little in common other than being lived copying the two ethnic groups and languages, should be evaluated in this study suggest that under separate headings. The field of our work in the year 2013 in accordance with the data obtained from the first one into the dialect characteristics of Turkish spoken in Lebanon, and the general features of the language used in the submitted article. Thus, in order to map received Turkish Language in Lebanon, based on the contribution to the field study aimed to achieve. Because the Turkish language is spoken within the borders of Lebanon, UNESCO's intangible cultural heritage are evaluated according to the criteria in the endangered languages program, "critically endangered" we have to mention that.